Analisis Common Size Untuk Menilai Kinerja Keuangan Perusahaan PT. Telekomunikasi Indonesia Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2022 - Maria Septiani Elisa Sugo; Yosefina Andia Dekrita; Maria Silvana Mariabel Carcia (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This research aimed to (1) discover financial performance by using common size analysis at PT. Telekomunikasi Indonesia is listed on the Indonesia Stock Exchange (IDX) for 2018-2022 in terms of the balance report, (2) understand how the financial performance is using common size analysis at PT. Telekomunikasi Indonesia is listed on the Indonesia Stock Exchange (IDX) for 2018-2022 in terms of profit and loss. This research type was descriptive research with a quantitative approach. The method employed in this research was common size analysis. The data used in this research was secondary data frome PT. Telekomunikasi Indonesia financial report documents from 2018-2022. The research findings of the financial performance assesed from the balance sheet for the asset component with the less-healthy categorization, the liability component with the less-healthy categorization, and the equity component with the unhealthy categorization. For financial, in terms of the income statement, it revealed that the income statement was in the unhealthy category.